On growth majorants of subharmonic functions - Yu. S. Protsyk; Ya. V. Vasyl’kiv (Математичні Студії)
We describe growth majorants of subharmonic in R^m (m≥2) functions. To do this, we exceptionally reduce the problem to problems in the theory of positive monotonous functions.